2022
DOI: 10.2196/33772
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social and App-Related Factors in Behavioral Engagement With mHealth for Improved Well-being Among Chronically Ill Patients: Scenario-Based Survey Study

Abstract: Background The last decade has seen a considerable increase in the number of mobile health (mHealth) apps in everyday life. These mHealth apps have the potential to significantly improve the well-being of chronically ill patients. However, behavioral engagement with mHealth apps remains low. Objective The aim of this study was to describe the behavioral engagement of chronically ill patients with mHealth apps by investigating (1) how it is affected by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Open access AI can also be used in public health management, for instance, use of mobile health apps in the rehabilitation of patients with chronic diseases 9 such as diabetes, 10 and stroke. 11 Moreover, some studies investigated the application of AI in diet, 12 sports 13 and emotional management.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Open access AI can also be used in public health management, for instance, use of mobile health apps in the rehabilitation of patients with chronic diseases 9 such as diabetes, 10 and stroke. 11 Moreover, some studies investigated the application of AI in diet, 12 sports 13 and emotional management.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 6 7 In addition, during the COVID-19 outbreak, the use of such aids as ultraviolet disinfectants and social robots was found to be effective in managing disease, treating patients and ensuring the safety of healthcare workers. 8 AI can also be used in public health management, for instance, use of mobile health apps in the rehabilitation of patients with chronic diseases 9 such as diabetes, 10 and stroke. 11 Moreover, some studies investigated the application of AI in diet, 12 sports 13 and emotional management.…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to perform a thorough and ongoing user survey to determine whether the monitoring application software used for remote healthcare is user-friendly in order to achieve and maintain these attributes [29] . One of the primary determinants for patient compliance in following the advice offered by medical professionals through the application, according to the most widely cited publishing journal in the bibliometric study above, is the appearance of a straightforward and understandable application [9] [30]. In-depth interviews with telemonitoring users and focus group discussions by users are suggested approaches to create an application display that is user-friendly and tailored to their preferences [31].…”
Section: Discussionmentioning
confidence: 99%
“…These features have been reported to be important in the uptake and continued use of health-related apps. 27 ) A report released by a software company claimed that only 8% of users continued to use medical and fitness apps 7 days after installation because of a lack of or poor engagement and functionality features (see https://www.braze.com/blog/app-customer-retention-spring-2016-report). Another study reported that most patients only use medical apps a few times after initial exposure.…”
Section: Discussionmentioning
confidence: 99%